Local government debt and economic growth in China - Yanrui Wu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
​China's local government debt (LGD) has recently become the focus of economic policy debates. However, information about LGD and its impact on economic growth in the Chinese economy is scarce. This paper attempts to present an empirical investigation of the impact of China's LGD on economic growth. It is probably the first of its kind to focus on China and thus contributes to the general literature on the relationship between government debt and economic growth. The paper first provides an assessment of LGD in China's regional economies, using recently released auditing statistics and other available secondary information. It then applies conventional growth analysis methods to examine the impact of LGD on regional growth in China. Various scenario and sensitivity analyses are also conducted, to accommodate the inadequacy and potentially poor quality of debt statistics. Publication
URN:NBN:fi:bof-201412193418
Keywords: O11; O53; H74; 330; local government debt; regional growth; China